Residential racial segregation and racial differences in sexual behaviours: an 11-year longitudinal study of sexual risk of adolescents transitioning to adulthood. - Biello, Katie Brooks; Niccolai, Linda; Kershaw, Trace S; Lin, Haiqun; Ickovics, Jeannette (Journal of epidemiology and community health, 2013)
Determining the underlying causes of racial disparities in sexually transmitted infections (STIs) is important. In the USA, rates of the most common STIs range from 5 to 20 times higher for African-Americans compared to Caucasians, and the health consequences of STIs can be serious. Residential racial segregation results in very different contexts for individuals and may be an important determinant of sexual risk. The purpose of this study was to examine how segregation and race interact to impact the age trajectory of sexual risk behaviours.
Keywords: Adolescent; Adult; African Americans; Age Factors; Child; European Continental Ancestry Group; Female; Health Status Disparities; Humans; Longitudinal Studies; Male; Outcome Assessment (Health Care); Racism; Residence Characteristics; Risk-Taking; Sex Factors; Sexual Behavior; Sexually Transmitted Diseases; Socioeconomic Factors; United States; Urban Population; Young Adult